Undergraduates Learn Evolution Through Teaching Kindergartners About Blind Mexican Cavefish - Gross, Joshua B. (CourseSource, 2016)
The development and implementation of a scientific outreach activity comes with a number of challenges. A successful outreach event must match the sophistication of content to the audience, be engaging, expand the knowledge base for participants, and be inclusive for a diverse audience. Ideally, a successful event will also convey the importance of scientific outreach for future scientists and citizens. In this paper, we present a simple, hands-on guide to a scientific outreach event targeted to kindergarten learners. This activity also pursued a second goal: the inclusion of undergraduate students in the development and delivery of the event. We provided a detailed set of four activities, focusing on the blind Mexican cavefish, which were enthusiastically received by kindergarten audiences. The engagement of undergraduate students in the development of this activity encouraged public outreach involvement and fostered new scientific and communication skills. The format of the outreach event we describe is flexible. We provide a set of guidelines and suggestions for adapting this approach to other biological topics. The activity and approach we describe enables the implementation of effective scientific outreach, using active learning approaches, which benefits both elementary school learners and undergraduate students.